Taking sides : - Newton , Lisa H. (McGrawHill, 2010)
This volume contains 40 selections, presented in a pro and con format, that debate a total of 20 different controversial issues in business ethics. In this book we ask you, the reader, to examine the accepted practices of business in the light of human needs, justice, rights, and dignity.